2021
DOI: 10.3390/ijerph18126303
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Heat Stress: Multi-Country Observations and Interventions

Abstract: Background: Occupational heat exposure can provoke health problems that increase the risk of certain diseases and affect workers’ ability to maintain healthy and productive lives. This study investigates the effects of occupational heat stress on workers’ physiological strain and labor productivity, as well as examining multiple interventions to mitigate the problem. Methods: We monitored 518 full work-shifts obtained from 238 experienced and acclimatized individuals who work in key industrial sectors located … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 48 publications
1
78
0
1
Order By: Relevance
“…Overall, the findings from the first study show that working under the sun increases skin temperature and the risk for experiencing clinical symptoms of heat strain, albeit without markedly altering physiological heat strain as defined by changes in core temperature and heart rate, even in cases where the level of environmental heat stress is considered to be the same as working in the shade. This is probably related to the well-described effect of self-pacing that is known to act proactively to avoid an increase in workers’ core body temperature [ 13 , 25 ]. However, self-pacing may not be appropriate when jobs or tasks are time-sensitive, involve productivity incentives, and/or involve workers who are not well trained in their job [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, the findings from the first study show that working under the sun increases skin temperature and the risk for experiencing clinical symptoms of heat strain, albeit without markedly altering physiological heat strain as defined by changes in core temperature and heart rate, even in cases where the level of environmental heat stress is considered to be the same as working in the shade. This is probably related to the well-described effect of self-pacing that is known to act proactively to avoid an increase in workers’ core body temperature [ 13 , 25 ]. However, self-pacing may not be appropriate when jobs or tasks are time-sensitive, involve productivity incentives, and/or involve workers who are not well trained in their job [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is probably related to the well-described effect of self-pacing that is known to act proactively to avoid an increase in workers’ core body temperature [ 13 , 25 ]. However, self-pacing may not be appropriate when jobs or tasks are time-sensitive, involve productivity incentives, and/or involve workers who are not well trained in their job [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investing in the health of migrant construction workers can directly benefit their health and productivity, and indirectly the success of countries and industries dependent on this population. Following simple, evidence based guidance at a construction site for the Qatar 2022 FIFA World Cup had substantial benefits for health and productivity 4142. As illustrated by the covid-19 pandemic, the costs of poorly managed outbreaks, lockdowns, and economic stimulus packages go far beyond the costs of effective public health responses 43…”
Section: Investing In Health and Social Conditionsmentioning
confidence: 99%
“…Big sporting events organised in hot regions expose migrant workers at the construction sites to hazards related to heat 42829. Studies on labour migrants at a construction site for the 2022 FIFA World Cup in Doha reported that people working outdoors in the sun spend most of their shift under high or extreme heat stress 430. The same research reported that the health risks of these workers were reduced in workplaces that implemented simple evidence based heat mitigation strategies, including providing shaded areas and requiring workers to carry water bottles throughout their shifts, worker educational programmes, and annual medical checks 430.…”
Section: Evidence On Health Needsmentioning
confidence: 99%